Respuestas

2013-09-25T19:40:28+02:00

Forma general de la ecuación
     y = b + ax
           b = ordenada en el origen
           a = pendiente
f(x) = 4x - 3
                           x                y = 4x - 3
                          -1                    - 7
                           0                    - 3
                           1                      1
Pendiente = 4
Ordenada en el origen = - 3

f(x) = 4 - 2x
                                 x                    y = 4 - 2x
                                -1                          6
                                 0                          4
                                 1                          2
Pendiente = - 2
Ordenada en el origen = 4